Handbook of transport strategy, policy and institutions - Button, Kenneth John; Hensher, David A., 1947- (Handbooks in transport, 2005)
Privatisation, regulation, deregulation, competition, funding, evaluation: these are all transport policy issues of great current interest worldwide, in the public arena as well as among researchers. In 46 chapters by acknowledged experts on their topics, these and other aspects of transport policy and planning are addressed in this, the sixth Handbook in Transport. The work is organised into sections covering:- Institutional Settings and Markets - Planning Perspectives - Asset Management and Funding - Regulatory Issues - Evaluation Frameworks - National StudiesWithin this section structure thi.